Linking environment and angling success at Humacao Natural Reserve lagoon system, Puerto Rico - Ferrer Montaño, Orlando; Dibble, Eric (Ciencia, 1970)
The Humacao Natural Reserve (HNR) lagoon system (Puerto Rico) provides surrounding communities with important fish resources where diverse fishery interests overlap. Fishes targeted include tarpon (Megalops atlanticus), snook (common snook Centropomus undecimalis and swordspine snook C. ensiferus), and tilapia (Mozambique tilapia Oreochromis mossambicus and redbreast tilapia Tilapia rendalli). We tested the utility of several meteorological, environmental, and biological variables as predictors of fishing success, represented by mean daily harvest per unit effort (HPUE) of creeled fishes with the intention of providing anglers of the HNR lagoon system with general assistance to improve harvesting. Values of HPUE and the remaining variables were generated as part of a broad project effort to evaluate the fisheries at HNR. Results of multiple regression analysis and canonical correspondence analysis indicated that it was possible to generate models amenable to biological, meteorological, and environmental interpretation. Most of the variables used in these analyses are easily gathered or observed by anglers; it appears that anglers willing to fish successfully at HNR would benefit from this type of information.